Determinants of international migration in Argentina: differences between European and Latin American inflows - Maurizio, Roxana (Iberoamerican Journal of Development Studies, 2014)
This paper studies, from a long-term perspective, the determinants of immigrant flows to Argentina from Europe and South America. Different econometric models are estimated for both the European waves –during the period from 1870 to 1950– and the Latin American waves –during the period from 1945 to 1976–. Results indicate a shift in the order of importance of the determinants of the entry rates, where the income gap, more than opportunities of employment differentials, appears to be the variable that generates the greatest reaction in the regional migratory flows. On the contrary, European flows seem to have been triggered by the second factor.